DEVELOPING STUDENTS' MEDIA LITERACY COMPETENCES BASED ON A CRITICAL INFORMATION EVALUATION PLATFORM (ON THE EXAMPLE OF THE CRITILEARN PLATFORM) (Universal International Scientific Journal, 2026)
This article analyzes the актуal problems of implementing research results intoeducational practice, their underlying causes, and possible solutions based on modern pedagogicalinnovations. In particular, the issue of developing students’ media literacy competence is substantiatedfrom a scientific and pedagogical perspective. The digital platform “CritiLearn” (Critical Learning),proposed by the author, is presented as a practical mechanism for integrating scientific developmentsinto the real educational process. The content of the platform, its methodological structure, modules,interface, and sample lesson designs are comprehensively described.
Keywords: scientific research; implementation into practice; pedagogical innovation